Productive Waqf Management as a Sustainable Fundraising Instrument in Islamic Boarding Schools: A Comparative Study - Agung Syarifudin; Ifan Syafiuddin; Abdul Wahid Wandana; Husni Munawar; Samiyono Samiyono (al-Afkar, Journal For Islamic Studies, 2026)
Among the most historically embedded faith-based educational institutions in the Muslim world, Indonesian Islamic boarding schools (pesantren) collectively enroll over four million students across nearly forty thousand establishments. Yet despite their deep social and pedagogical significance, most pesantren operate under persistent financial fragility, relying heavily on inconsistent tuition fees, charitable donations, and modest state allocations conditions that fundamentally undermine their long-term institutional viability. Productive waqf (wakaf produktif), an endowment mechanism whereby dedicated assets are actively managed through commercial activity to generate recurring income, has increasingly gained attention as a structurally sound response to this chronic underfunding. This article presents a comparative examination of productive waqf management practices across selected Indonesian pesantren, with particular attention to institutional configurations, governance arrangements, asset deployment strategies, and financial performance. Employing qualitative case study methodology alongside documentary analysis, the research draws on evidence from financially high-performing institutions to evaluate effective practices and their potential applicability within less-resourced pesantren contexts. The findings reveal that sustainable financial outcomes are most strongly associated with professionally structured nazhir governance, formal legal certification of waqf assets, and diversified endowment portfolios. Theoretically, this study advances scholarship at the intersection of Islamic social finance and educational management by offering a comparative governance framework with broader relevance to Islamic philanthropic finance.